Does Team Based Learning (TBL) in the Pharmacy Classroom Foster Leadership Skills in the Workplace? - Robert C. Haight; Marta J. Brooks (INNOVATIONS in Pharmacy, 2022)
Objective: A well-functioning healthcare team is important to optimizing the health outcomes of patients. As such, the use of Team Based Learning (TBL) in the education of health professionals has emerged as one of the more common active learning strategies. In various anecdotes with preceptors, it had been observed that student pharmacists educated in a TBL classroom exhibited increased skills in the affective domain. This qualitative pilot study begins to examine affective domain skills that are important to pharmacy practice and which of those skills may be developed uniquely through TBL.